Learning and Instructional Technologies for the 21st Century Visions of the Future - Moller, Leslie; Huett, Jason Bond.; Harvey, Douglas M.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Learning and Instructional Technologies for the 21st Century gathers research which identify models and approaches to improve learning through the inclusion of technology. These papers, from leading researchers and thinkers in instructional technology, begin by refuting the idea that education can be improved through more or better technology. Instead, the contributors emphasize specific, research-based ideas, which re-evaluate learning, reorganize schools, redirect technology, and provide instruction. Acknowledging the critical role of technology, these contributions explore technology's main advantage--its ability to enable advanced learning designs and emerging paradigms as well as to evolve learning interactions. While each paper explores a specific aspect of the role of technology, the collection shares this common theme. Without sufficient consideration to the process of learning and its many facets, technological availability alone will not provide a sustained impact on the educational process. Originating from the first AECT Research Symposium, Learning and Instructional Technologies for the 21st Century will be of interest to researchers and practitioners alike.
Adventures and Advances in Instructional Design Theory and Practice -- Coming at Design from a Different Angle: Functional Design -- Robust Designs for Scalability -- Externally Modeling Mental Models -- Applying a Critical and Humanizing Framework of Instructional Technologies to Educational Practice -- When a Peer Group Isn#x2019;t Needed: Effective Online Learning in an Individual Mentoring Model -- Linking the POV-ing Theory to Multimedia Representations of Teaching, Learning, Research in the Age of Social Networking -- Creating Shared Visions of the Future for K-12 Education: A Systemic Transformation Process for a Learner-Centered Paradigm -- Technology as a Change Agent in the Classroom -- Using Activity Theory to Evaluate and Improve K-12 School and University Partnerships -- Reflections: Variations on a Theme -- Reflections: Variation on a Theme: Part 2 Is This Jazz, or Are We Singing the Blues?.
Keywords: Education; Education -- Data processing; Educational technology; Education; Educational Technology; Computers and Education; Learning & Instruction; Electronic books